Analisis Perbedaan Perilaku Impulse Buying Konsumen Laki-Laki dan Perempuan Berdasarkan Proses Afektif dan Kognitif - Tooy, Stephanie M (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The purpose of this study is to know the differences of impulse buying behavior between male and female based on affective process, cognitive process and categories of product purchased.. The result of independent sample t test analysis shows males are more dominant in irresistible urge to buy, disregard for the future, and product categories purchased (coats, electronics, hardware, computer software and sports memorabilia) while females are more dominant in positive buying emotion, mood management, cognitive deliberation, unplanned buying, overall affective and cognitive process, and product categories purchased (shirts/sweaters, pants/skirts, business wear, underwear, accessories, shoes, CD/DVD, entertainment, health and beauty, and magazines/books), there is no significant difference between male and female in affective and cognitive process components, overall affective and cognitive process, product categories purchased (shirts/sweaters, pants/skirts, business wear, underwear, accessories, shoes, CD/DVD, sports memorabilia, entertainment, health and beauty, and magazines/books), and there is significant difference between male and female in product categories purchased (coats, electronics, hardware, and computer software). Keywords:       Gender, Affective, Cognitive, Impulse Buying.